One-component latent cold-applied sealing paste and preparation method thereof
By using the formula of a single-component latent variant cold construction sealing paste in the sealing paste, combined with petroleum asphalt, thermoplastic elastomer and other materials, the problem of waterproofing function loss of the sealing paste under stress relaxation and deformation is solved, and high latent degeneration and Good adhesion simplifies the construction process.
Patent Information
- Application Number
- CN202210988938.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-17
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-08-17
AI Technical Summary
The existing sealing paste loses its waterproof function due to stress relaxation and deformation after construction, and has poor weather resistance and low temperature flexibility, and the multi-component construction process is cumbersome.
Using a single-component latent variant cold construction sealing paste, the formula includes petroleum asphalt, thermoplastic elastomer, styrene butadiene rubber, petroleum resin, fiber, wax, filler and D series solvent oil. The sealing paste is ensured through specific formula ratios and process flows. It has good weather resistance and latent degeneration.
It realizes that the sealing paste maintains good waterproof performance in high and low temperature environments, has high latent denaturation and good adhesion, avoids loss of function caused by stress relaxation and deformation, and simplifies the construction process and reduces costs.
Smart Images

Figure CN115449342B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and more specifically, relates to a single-component latent cold construction sealing paste and a preparation method thereof. Background Art
[0002] At present, in waterproof construction, due to the concrete construction itself or the bonding between the roll material and the base layer, various gaps or unsatisfactory bonding appear, which seriously affects the overall construction quality of waterproof construction and increases the difficulty of construction. Although there are some caulking products, such as water-based waterproof coatings and solvent-based caulking materials, these materials usually lose their own performance a few years after the construction is completed because they need to undergo weather resistance and deformation tests after construction. New cracks appear, causing the waterproof function to be lost or reduced again. Existing caulking products such as sealants will experience stress relaxation over time after construction and are difficult to recover after deformation. The deformation is irreversible or the recovery is small, and it is easy to break or separate from the sealed material.
[0003] The existing single-component sealant is made of plastic raw materials in consideration of the need for good construction performance. After construction and molding, it will crack due to thermal expansion and contraction with the change of seasons, lose its waterproof function, and has poor weather resistance and low-temperature flexibility, which requires further repair. Existing creep-type sealing materials are often three or more components. Before construction, the components need to be mixed together, the curing time needs to be calculated, and all the ingredients need to be used up at one time, otherwise the remaining materials can only be discarded.
[0004] Therefore, it is necessary to improve the performance of sealing materials such as sealants. They need to have excellent weather resistance and latent deformation resistance, and be able to meet the tests of seasonal changes and various stresses. Summary of the invention
[0005] The purpose of the present invention is to provide a one-component latent cold construction sealing paste and a preparation method thereof. The sealing paste of the present invention has good weather resistance and latent property, is convenient to construct, and can be constructed at room temperature.
[0006] In order to achieve the above-mentioned purpose, one aspect of the present invention provides a one-component latent cold-applied sealant, the raw materials for preparing the sealant include: petroleum asphalt, thermoplastic elastomer, styrene-butadiene rubber, petroleum resin, fiber, wax, filler and D series solvent oil.
[0007] According to the present invention, preferably, by weight, the petroleum asphalt is 25-40 parts, the thermoplastic elastomer is 1-3 parts, the styrene-butadiene rubber is 1-5 parts, the petroleum resin is 1-4 parts, the fiber is 2-4 parts, the wax is 2-4 parts, the filler is 35-45 parts and the D series solvent oil is 17-26 parts.
[0008] In the present invention, raw materials with moderate molecular weight (thermoplastic elastomer, styrene-butadiene rubber) are selected to keep the whole system with relatively controllable strength, so as not to make the strength too high and affect the construction performance. At the same time, cross-linked materials (fiber materials, which play a reinforcing role, can well gather various materials in the system to ensure that they do not flow at high temperatures) are introduced to ensure that no deformation occurs at high temperatures without external forces. In addition, there are no volatile substances and reactive active substances in the system, which ensures that the whole system is stable, not easy to oxidize, and can be stored for a long time.
[0009] In the present invention, by adding high elastic materials such as styrene-butadiene rubber and thermoplastic elastomer, the elastic recovery rate of the prepared sealing paste is close to 100%, and after construction, it shows a high latent property, which conforms to the stress-strain characteristics of the typical latent curve, such as Figure 1 As shown in the typical latent curve, as time goes by and deformation occurs, the stress remains unchanged, so that the finished waterproof sealing product with high latent property will not break or separate from the sealed material, and always has the waterproof function.
[0010] In the present invention, the elastomeric material with a moderate molecular weight has excellent elasticity itself, which can make the whole system have excellent elasticity, showing good low-temperature performance. With the introduction of the reinforcing material, there is a certain cohesion in the whole system, and the elastomeric material itself also has a certain cohesion, ensuring that the whole system will not undergo a large deformation at a higher temperature, avoiding flow and loss of high-temperature performance. The introduction of some low-activity substances such as low-grade asphalt increases the oxidation resistance of the whole system, ensuring that the whole system will not lose its good high latent deformation due to oxidation for a long time.
[0011] According to the present invention, preferably, the petroleum asphalt is 70# petroleum asphalt and / or 90# petroleum asphalt.
[0012] According to the present invention, preferably, the thermoplastic elastomer is a linear SBS and / or a linear SIS;
[0013] The number average molecular weight of the thermoplastic elastomer is 80,000-120,000.
[0014] According to the present invention, preferably, the styrene-butadiene rubber is SBR and / or SSBR;
[0015] The number average molecular weight of the styrene-butadiene rubber is 100,000-150,000.
[0016] According to the present invention, preferably, the petroleum resin is C5 petroleum resin and / or C9 petroleum resin.
[0017] According to the present invention, preferably, the fiber is at least one of polyester fiber, glass fiber and lignin fiber;
[0018] The length of the fibers is 1.0-1.5 cm.
[0019] According to the present invention, preferably, the wax is at least one of soybean wax, paraffin wax and polyethylene wax;
[0020] The filler is at least one of heavy calcium, mineral powder, light calcium and talcum powder.
[0021] According to the present invention, preferably, the D series solvent oil is at least one of D80, D90 and D100 environmentally friendly solvent oils.
[0022] Another aspect of the present invention provides a method for preparing the above-mentioned sealing paste, the preparation method comprising:
[0023] (1) stirring the petroleum asphalt uniformly at a temperature of 130-140° C.;
[0024] (2) adding the styrene-butadiene rubber to the petroleum asphalt, maintaining the temperature at 130-140° C., and stirring evenly;
[0025] (3) adding the petroleum resin, stirring evenly, and maintaining the temperature at 140-150° C.;
[0026] (4) adding the wax, stirring evenly, and maintaining the temperature at 150-160° C.;
[0027] (5) adding the thermoplastic elastomer, stirring evenly, and maintaining the temperature at 170-180° C.;
[0028] (6) Add the filler, stir evenly, and maintain the temperature at 100-110° C.;
[0029] (7) Add the D series solvent oil, stir evenly, and maintain the temperature at 70-90° C.;
[0030] (8) Add the fiber and stir evenly to obtain the sealing paste.
[0031] The technical solution of the present invention has the following beneficial effects:
[0032] (1) The one-component latent cold-applied sealant of the present invention introduces materials with good high and low temperature performance such as styrene-butadiene rubber and thermoplastic elastomer, so that the system itself has excellent high and low temperature performance, thereby ensuring that it has good weather resistance, does not flow at high temperatures, and does not crack at low temperatures, ensuring that it does not lose its own performance during the engineering warranty period, and ensuring the integrity of the entire waterproof system.
[0033] (2) The one-component latent cold-applied sealing paste of the present invention has good latent properties, so that it has good ductility and adhesion when the deformation joint is deformed, and at the same time does not produce stress relaxation. After the deformation joint is deformed, it can still ensure that the gap is completely filled.
[0034] (3) The one-component latent cold-applied sealant of the present invention is a one-component cold-applied sealant, which eliminates the cumbersome process of multi-component construction and does not require heating. It can be used immediately after opening the barrel, which is energy-saving and environmentally friendly while reducing the manpower and material resources of construction.
[0035] (4) The one-component latent cold-applied sealant of the present invention solves the problem that the previous sealant cannot withstand stress and deformation for a long time. At the same time, due to the selection of raw materials, the entire system passes the test in the 100% cohesive failure test (tensile adhesion), indicating that it has good viscosity and is well bonded to the base surface or the sealed object and is not easy to separate. In terms of water blocking, it can withstand a pressure exceeding 0.3MPa and has a good water blocking effect.
[0036] (5) The one-component latent cold-applied sealing paste product of the present invention increases the durability of the entire waterproof system, strengthens the waterproof ability, and reduces the cost of use, reflecting good economic and social benefits.
[0037] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.
[0039] Figure 1 A typical latent curve diagram in the prior art is shown. DETAILED DESCRIPTION
[0040] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0041] The present invention is further described below by examples:
[0042] The SBR used in the following examples and comparative examples is powdered styrene-butadiene rubber purchased from Shandong Gaoshi Science and Technology Industry and Trade Co., Ltd., with a number average molecular weight of 120,000; the SBS is linear SBS with a number average molecular weight of 100,000 purchased from Dushanzi Petrochemical Company, with a brand name of T6302H.
[0043] The lengths of the lignin fibers, glass fibers and polyester fibers used in the following examples and comparative examples are all 1.0-1.5 cm.
[0044] The amounts of the raw materials used in the following examples and comparative examples are in parts by weight.
[0045] Example 1
[0046] Stir 34 parts of 70# petroleum asphalt at 140℃ for standby use, add 3 parts of SBR to 70# petroleum asphalt, maintain the temperature at 140℃ and stir evenly, stir at 500rpm, stir for 30 minutes, add 2 parts of C5 petroleum resin and continue stirring for 10 minutes, maintain the temperature at 140℃, add 2 parts of polyethylene wax and continue stirring for 30 minutes, maintain the temperature at 150℃, add 2 parts of SBS and continue stirring for 120 minutes, maintain the temperature at 180℃, add 40 parts of 200 mesh talcum powder and continue stirring for 10 minutes, stir at 1200rpm, maintain the temperature at 110℃, add 17 parts of D80 environmentally friendly solvent oil and continue stirring for 10 minutes, maintain the temperature at 80℃, add 2 parts of lignin fiber and continue stirring for 10 minutes. The finished product is ready for testing.
[0047] Example 2
[0048] Stir 31 parts of 90# petroleum asphalt at 140℃ for use, add 4 parts of SBR to 90# petroleum asphalt, maintain the temperature at 140℃ and stir evenly, stir at 500rpm, stir for 30 minutes, add 3 parts of C5 petroleum resin and continue stirring for 10 minutes, maintain the temperature at 140℃, add 3 parts of polyethylene wax and continue stirring for 30 minutes, maintain the temperature at 150℃, add 2 parts of SBS and continue stirring for 120 minutes, maintain the temperature at 180℃, add 38 parts of 200 mesh talcum powder and continue stirring for 10 minutes, stir at 1200rpm, maintain the temperature at 110℃, add 17 parts of D80 environmentally friendly solvent oil and continue stirring for 10 minutes, maintain the temperature at 80℃, add 2 parts of glass fiber and continue stirring for 10 minutes. The finished product is ready for testing.
[0049] Example 3
[0050] Stir 32 parts of 70# petroleum asphalt at 140℃ for use, add 2 parts of SBR to 70# petroleum asphalt, maintain the temperature at 140℃ and stir evenly, stir at 500rpm, stir for 30 minutes, add 1 part of C5 petroleum resin and continue stirring for 10 minutes, maintain the temperature at 140℃, add 2 parts of polyethylene wax and continue stirring for 30 minutes, maintain the temperature at 150℃, add 3 parts of SBS and continue stirring for 120 minutes, maintain the temperature at 180℃, add 41 parts of 200 mesh talcum powder and continue stirring for 10 minutes, stir at 1200rpm, maintain the temperature at 110℃, add 17 parts of D80 environmentally friendly solvent oil and continue stirring for 10 minutes, maintain the temperature at 80℃, add 2 parts of polyester fiber and continue stirring for 10 minutes. The finished product is ready for testing
[0051] Example 4
[0052] Stir 31 parts of 90# petroleum asphalt at 140℃ for standby use, add 1 part of SBR to 90# petroleum asphalt, maintain the temperature at 140℃ and stir evenly, stir at 500rpm, stir for 30 minutes, add 2 parts of C5 petroleum resin and continue stirring for 10 minutes, maintain the temperature at 140℃, add 2 parts of polyethylene wax and continue stirring for 30 minutes, maintain the temperature at 150℃, add 2 parts of SBS and continue stirring for 120 minutes, maintain the temperature at 180℃, add 41 parts of 200 mesh talcum powder and continue stirring for 10 minutes, stir at 1200rpm, maintain the temperature at 110℃, add 17 parts of D80 environmentally friendly solvent oil and continue stirring for 10 minutes, maintain the temperature at 80℃, add 4 parts of polyester fiber and continue stirring for 10 minutes. The finished product is ready for testing.
[0053] Comparative Example 1
[0054] Stir 32 parts of 70# petroleum asphalt at 140℃ for use, add 7 parts of C5 petroleum resin and stir for 10 minutes, maintain the temperature at 140℃, add 2 parts of polyethylene wax and continue stirring for 30 minutes, maintain the temperature at 140℃, add 40 parts of 200 mesh talcum powder and continue stirring for 10 minutes, stirring speed 1200rpm, maintain the temperature at 110℃, add 17 parts of D80 environmentally friendly solvent oil and continue stirring for 10 minutes, maintain the temperature at 80℃, add 2 parts of glass fiber and continue stirring for 10 minutes. The finished product is ready for testing.
[0055] Comparative Example 2
[0056] At 140°C, stir 33 parts of 70# petroleum asphalt evenly for use, add 6 parts of C5 petroleum resin and continue stirring for 10 minutes, maintain the temperature at 140°C, add 2 parts of polyethylene wax and continue stirring for 30 minutes, maintain the temperature at 140°C, add 40 parts of 200 mesh talcum powder and continue stirring for 10 minutes, stirring speed 1200rpm, maintain the temperature at 110°C, add 17 parts of D80 environmentally friendly solvent oil and continue stirring for 10 minutes, maintain the temperature at 80°C, add 2 parts of glass fiber and continue stirring for 10 minutes. The finished product is ready for testing.
[0057] Test Case
[0058] This test example tests the sealing pastes of Examples 1-4 and Comparative Examples 1-2; wherein, the water-tightness test and tensile adhesion test are conducted according to the JC / T2428-2017 standard, the low-temperature flexibility and heat resistance are tested according to the JC / T408-2005 standard, and the latent deformation test is conducted according to the GB / T 10120-2013 standard. The latent deformation test specimens need to be placed in a 130-degree oven for 3 hours in advance. The test results are shown in the following table:
[0059] Table 1
[0060]
[0061]
[0062] As can be seen from Table 1, Examples 1 and 2 can meet the requirements in various test indicators, and both show good high latent deformation. In the latent deformation experiment, there is no obvious stress relaxation phenomenon within the specified time, indicating that the material itself has the ability to solve technical problems such as damage caused by stress relaxation and separation from the base surface, and can continue to have a good waterproof effect under deformation and external force. Example 2 is better than Example 1 in low temperature, because more styrene-butadiene rubber and thermoplastic elastomer are added, so that the whole system shows better low temperature resistance. Examples 3 and 4 reduce the amount of elastomer, and slight stress relaxation occurs. Comparative Examples 1 and 2 have a certain rigidity because there is no introduction of elastomer, so stress damage occurs; in low temperature flexibility and tensile adhesion, it can also be seen that there are obvious differences. Although Examples 1-4 all meet the requirements, there are differences in performance.
[0063] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A one-component latent cold-applied sealing paste, characterized in that: The raw materials for preparing the sealing paste include: petroleum asphalt, thermoplastic elastomer, styrene-butadiene rubber, petroleum resin, fiber, wax, filler and D series solvent oil; Wherein, by weight, the petroleum asphalt is 25-40 parts, the thermoplastic elastomer is 1-3 parts, the styrene-butadiene rubber is 1-5 parts, the petroleum resin is 1-4 parts, the fiber is 2-4 parts, the wax is 2-4 parts, the filler is 35-45 parts and the D series solvent oil is 17-26 parts; The fiber is at least one of polyester fiber, glass fiber and lignin fiber; The length of the fiber is 1.0-1.5 cm; The number average molecular weight of the thermoplastic elastomer is 80,000-120,000; the number average molecular weight of the styrene-butadiene rubber is 100,000-150,000; The thermoplastic elastomer is linear SBS and / or linear SIS; The filler is at least one of heavy calcium, light calcium and talcum powder.
2. The sealing paste according to claim 1, wherein The petroleum asphalt is 70# petroleum asphalt and / or 90# petroleum asphalt.
3. The sealing paste according to claim 1, wherein The styrene-butadiene rubber is SBR and / or SSBR.
4. The sealing paste according to claim 1, wherein The petroleum resin is C5 petroleum resin and / or C9 petroleum resin.
5. The sealing paste according to claim 1, wherein The wax is at least one of soybean wax, paraffin wax and polyethylene wax.
6. The sealing paste according to claim 1, wherein The D series solvent oil is at least one of D80, D90 and D100 environmentally friendly solvent oils.
7. The method for preparing the sealing paste according to any one of claims 1 to 6, characterized in that: The preparation method comprises: (1) stirring the petroleum asphalt uniformly at a temperature of 130-140° C.; (2) adding the styrene-butadiene rubber into the petroleum asphalt, maintaining the temperature at 130-140° C., and stirring evenly; (3) Add the petroleum resin, stir evenly, and maintain the temperature at 140-150°C; (4) Add the wax, stir evenly, and maintain the temperature at 150-160°C; (5) Add the thermoplastic elastomer, stir evenly, and maintain the temperature at 170-180°C; (6) Add the filler, stir evenly, and maintain the temperature at 100-110°C; (7) Add the D series solvent oil, stir evenly, and maintain the temperature at 70-90°C; (8) Add the fiber and stir evenly to obtain the sealing paste.
Citation Information
Patent Citations
Self-glued asphalt adhesive material, preparation method of self-glued asphalt adhesive material, and self-glued asphalt waterproof coiled material
CN106398244A